2000
DOI: 10.1007/s004020050473
|View full text |Cite
|
Sign up to set email alerts
|

The initial fixation of the press-fit acetabular shell - clinical observation and experimental study

Abstract: The initial solid fixation of an uncemented acetabular component affects the amount of bone ingrowth. We had several problems with broken screws in cases of acetabular revision. In recent years, the development of uncemented components without screws has attempted to improve these problems. We started to use "press-fit"-type acetabular shells in November 1996. Our thirty cases undergoing 2 mm under-reaming show good initial stability. The aim of our biomechanical study was to assess the most suitable degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Underreaming by 2 mm increased this torsion to failure to approximately 28 Nm. Others have reported similar results [4]. Based on these calculations, depending on the patient's weight, activity level, component positioning, and amount of offset used, the torsional forces applied to the component could very well exceed that required to result in failure of initial fixation.…”
Section: Discussionmentioning
confidence: 79%
“…Underreaming by 2 mm increased this torsion to failure to approximately 28 Nm. Others have reported similar results [4]. Based on these calculations, depending on the patient's weight, activity level, component positioning, and amount of offset used, the torsional forces applied to the component could very well exceed that required to result in failure of initial fixation.…”
Section: Discussionmentioning
confidence: 79%
“…Regarding the press-fit technique in cementless THA, Kaneko et al [2] reported good clinical results and roentgenogram evaluations for 30 uncemented acetabular cups with 2-mm under-reaming, as well as good stability on biomechanical compression load and twist testing. Ng et al [4] reported the 2- to 6-year results of 74 THAs using a cementless acetabular component without holes for supplemental screw fixation and the immediate full-weight-bearing walking allowed postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning both fixation techniques, some reports place emphasis on press-fit fixation [26], while others note that bone screws are very helpful aids in cup fixation [710]. However, those studies reported the benefits and limitations of press-fit and screw fixation independently.…”
Section: Introductionmentioning
confidence: 99%
“…in the case of osteoporotic bone or a dysplastic acetabulum. The use of additional screws when implanting cementless cups in primary hip arthroplasty continues to be the subject of considerable debate in the literature [7][8][9][10][11][12][13]. In their investigations in 2015, Tabata et al showed that the additional use of screws increased the primary stability of the cup [10].…”
Section: Introductionmentioning
confidence: 99%